The Effect of Using Youtube Videos on Students' Writing Descriptive Text Across Learning Styles - Rakhmad Felanie (Pascasarjana Universitas Negeri Malang, 2021)
Abstract: Investigating the effect of using Youtube videos toward student's writing descriptive text across student's learning styles is the objective of this research. The research is quasi-experimental factorial research. Non-randomized sampling technique was applied in this research. The sample of the research were 10th grade of Multimedia 1 class student. The Instrument used in this research were pretest and posttest as means to measure students' writing achievement, and questionnaire as means to identify students' learning styles. Two way Anova (Analysis of Variance) was used to analyze the data.  It was found that the achievement of students who were taught using Youtube videos were higher than the students who were not taught by using Youtube videos. Writing achievement of visual learning style students were better than auditory learning style students in experimental class. It was also found that the significant value of interaction between the usage Youtube videos and student writing achievement was .04. The significant level was less than .05 (04< .05). However, learning style has no effect to writing achievement. Abstrak: Meneliti pengaruh penggunaan video YouTube terhadap prestasi menulis teks deskriptif siswa dihubungkan dengan gaya belajar mereka adalah tujuan dari penelitian ini. Peneliatian ini adalah penelitian kuasi eksperimental. Sampel non acak diterapkan dalam penelitian ini. Sampel dari penelitian adalah siswa kelas 10 Multimedia. Instrument yang dipakai dalam penelitian ini adalah pretest dan posttest sebagai alat mengukur prestasi menulis siswa dan angket sebagai alat mengidentifikasi gaya belajar siswa. Two way Anova digunakan untuk menganalisa data. Ditemukan bahwa prestasi siswa yg diajar menggunakan video YouTube lebih baik prestasinya daripada siswa yang tidak menggunakan video YouTube. Prestasi menulis siswa gaya belajar visual lebih baik daripada siswa gaya belajar audio di dalam grup ekperimental. Ditemukan juga nilai signinfikan dari interaksi antara penggunaan video YouTube dan prestasi menulis siswa sebesar 0.4. Level signifikan kurang dari .05 (04< .05). Akan tetapi, learning style tidak berpengaaruh kepada prestasi menulis.